Developing a Rubric for Teacher`s Self-Efficacy and Teaching Competency in Drug Education Based on the ADDIE Model - Ahmad Jazimin Jusoh; Nazre Abdul Rashid; Ciptro Handrianto (Peneliti.net, 2022)
The drug prevention programs in school were conducted in curricular and co-curricular activities by involving all parties to participate such as head masters, administration staffs, teachers, students and parents. In terms of curriculum, classroom teachers had significant role in drug education to integrate their teaching-learning topics with drug abuse prevention among students. This study aimed to use analysis, design, development, implementation and evaluation (ADDIE) model to develop the rubric for teacher`s self-efficacy and teaching competency in drug education. The methodology used in this was research and development research by using ADDIE Model to enable the system to achieve the educational rubric in assessing teachers` self-efficacy and teaching competency in drug education. The results indicated that the use of ADDIE Model matched to develop the rubric to assess efficacy and competency of classroom teachers in integrating drug prevention topics in teaching-learning situation following five phases. The study concluded that the ADDIE model can be adopted to develop assessment tools to measure teacher`s abilities and it helps to improve teacher`s self-efficacy and teaching competency in drug education in Malaysian secondary schools.